A mission‐based architecture for swarm unmanned systems. Issue 3 (10th February 2019) - Giles, Kathleen; Giammarco, Kristin
Abstract: This research applies a mission engineering approach with model‐based systems engineering foundations to formalize a swarm unmanned system design methodology and architecture. The architectural framework and methodology herein presented extend current swarm system design methods, which are primarily bottom‐up approaches focused on the behavior of individual agents. We introduce a top‐down, hierarchical approach with an overarching mission decomposed into phases, tactics, plays, and algorithms. Three unmanned aerial vehicle swarm case studies (one of which is discussed in this paper) are used to demonstrate the approach and its effectiveness in formalizing a mission‐based framework of common patterns in swarm missions that promote architecture reusability.